Taxonomy coordinates of anticorruption expertise - E. A. Akunchenko (Russian Journal of Economics and Law)
Objective: to develop scientifically sound proposals for determining the taxonomic coordinates of anti-corruption expertise among other types of expertise.Methods: the general scientific method of dialectical cognition, as well as a number of specific scientific methods, such as system-structural, comparative-legal, formal-logical (deduction, induction, definition and division of concepts), statistical, etc.Results: based on the analysis of approaches proposed in the scientific literature to understanding anti-corruption expertise and its relationship to other taxonomic units (legal, judicial and criminological expertise), the author concludes that this institution is complex and represents an independent phenomenon that is not identical to any of the above types of expertise. According to the author, the regulatory framework defined in a special federal law actually restricts scholars in studying the anti-corruption expertise development prospects as an element of the Russian anti-corruption system, and practitioners – in its effective application with a view of identifying and eliminating corruption-causing factors. In order to overcome the current scientific stagnation, it is necessary to rethink the essence and nature of anti-corruption expertise on a new methodological basis and take into account current taxonomic coordinates.Scientific novelty: the idea is substantiated that the current model of anti-corruption expertise of normative legal acts and their drafts needs to be transformed in order to move to a qualitatively new level. It allows assessing for the presence of corruption-causing factors not only the regulatory impact of legal norms, but also any transformative activity of social management subjects. In this regard, it is proposed to consider the institute of anti-corruption expertise as a promising object of cognition within the structure of the anti-corruption security theory.Practical significance: the presented results of studying the taxonomic coordinates of anti-corruption expertise can be used for a qualitative transformation of the theory and practice of expert activity, as well as in determining the main directions for improving the effectiveness of this institution while preparing a new National anti-corruption plan for the near future.